An analysis of the Agama atra complex (Reptilia: Agamidae) in Namaqualand and Southern Namibia - Flemming, A. F.(Alexander Frederik) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1996.